2019
DOI: 10.1039/c9qm00208a
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid crystals with aggregation-induced emission properties based on pyrrolo[3,2-b]pyrrole salt compounds

Abstract: The emission behaviors of AIE–ILC molecules (DPP-2Py-9) in different aggregation states were affected by their molecular stacking arrangements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Due to the change in aggregation mode at various temperatures, the ILC showed temperature-dependent fluorescence. 155 On the basis of a similar mechanism, Ren et al reported ILCs with temperature-dependent fluorescence, which was composed of 1:4 supramolecular complexes of four carboxylate-bearing tetraphenylethenes and dimethyldioctadecylammonium which exhibited an LC phase with a helical column that packed in a monoclinic lattice. 156,157 To change the fluorescence profiles of ILCs with an AIE nature, not only a temperature change but also various external stimuli are applicable.…”
Section: The Conduction Of Ions and Protonsmentioning
confidence: 98%
“…Due to the change in aggregation mode at various temperatures, the ILC showed temperature-dependent fluorescence. 155 On the basis of a similar mechanism, Ren et al reported ILCs with temperature-dependent fluorescence, which was composed of 1:4 supramolecular complexes of four carboxylate-bearing tetraphenylethenes and dimethyldioctadecylammonium which exhibited an LC phase with a helical column that packed in a monoclinic lattice. 156,157 To change the fluorescence profiles of ILCs with an AIE nature, not only a temperature change but also various external stimuli are applicable.…”
Section: The Conduction Of Ions and Protonsmentioning
confidence: 98%
“…An important tool to classify these interactions are the so‐called Hofmeister series of cations and anions (also called lyotropic series), the discovery of which goes back to Franz Hofmeister in 1887 [32] . Cations and anions are ranked in two separate series according to their interaction with a solvent, specifically water [33–39] . The ability which ranks the ions in the Hofmeister series is called chaotropy.…”
Section: Ilc Mesomorphismmentioning
confidence: 99%
“…AIE‐active ILCs were also obtained by combining pyridinium salts with wedge‐shaped appendages (Scheme 7, 12(X′′) ) [139] . Dong developed pyrrolo[3,2‐b]pyrrole ILCs with two pyridinium units at the peripheral rings, which were not AIE‐active but showed a stepwise increase of the photoluminescence intensity at the phase transition SmA to Cr upon cooling from the isotropic liquid (Scheme 7, 13 ) [35] …”
Section: Novel Mesogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the past decades, fluorescent LCs are receiving increasing attention, since the combination of the ability to emit light and spontaneously self-assemble into mesoscopic structures is promising for optoelectronic applications, such as anisotropic light-emitting diodes and emissive liquid crystal displays. Depending on the molecular alignment in the mesophase (nematic or chiral-nematic), fluorescent LCs may emit linear or circular polarized light. However, a major problem in the development of novel fluorescent liquid crystals is that, typically, the fluorescence emission is dramatically reduced during the formation of the ordered phase (mesophase or crystalline state). , This challenge can be overcome by the use of aggregation-induced emission (AIE) chromophores. These chromophores exhibit a rotorlike structure, allowing high rotational mobility in organic solvents, converting absorbed light into motion and a resultant loss in emission. However, upon aggregation, intramolecular motion (RIM) or intramolecular rotation (RIR) is restricted, triggering fluorescence or phosphorescence emission.…”
mentioning
confidence: 99%